Polycythaemia rubra vera transforming to acute lymphoblastic leukaemia with a common immunophenotype. - Neilson, J R (1994)
Lymphoblastic transformation of polycythaemia rubra vera is an extremely rare phenomenon. A case of a 76 year old man with polycythaemia rubra vera who developed acute lymphoblastic leukaemia (ALL) 16 years after his initial diagnosis is reported. Membrane markers showed a CD10 positive (common ALL) immunophenotype. To our knowledge this association has not been previously recorded. The rare occurrence of ALL in polycythaemia rubra vera may indicate that in a minority of patients clonal expansion of an abnormal pluripotent haemopoietic stem cell is responsible for the polycythaemia rubra vera disease phenotype.